Histopathological Features and Composition of Gut Microbiota in Rhesus Monkey of Alcoholic Liver Disease - Wang, Hong; Yan, Yaping; Yi, Xiaoyan; Duan, Yanchao; Wang, Junfeng; Li, Shanshan; Luo, Lilin; Huang, Tianzhuang; Inglis, Briauna; Li, Xi; Ji, Weizhi; Tan, Tao; et al. (Frontiers in Microbiology, 2019)
Alcohol-induced chronic liver disease (ALD) is becoming the most prevalent liver disease in the world. However, the etiology of ALD remains blurry and there are no effective, universally accepted therapies for ALD currently. Historical evidence has demonstrated a link between gut microbiota and the liver. But it is difficult to distinguish the effect of gut microbiota changes caused by alcohol consumption in humans since the microbiota change detected in humans is complicated by diet and environmental factors. In contrast, the diet and environmental conditions can be controled well in nonhuman primate models with ALD. Due to the genetic, physiological, metabolic and behavioral similarities to human, the rhesus monkey provides excellent translational validity in preclinical studies. In the present study, we generated a rhesus monkey model of alcohol induced liver steatosis that is compatible with the clinical progression of the biochemistry and pathology in humans with ALD. We explored the relationship between ALD and the gut microbiome in the rhesus monkeys with alcoholic liver steatosis. Our results showed that the change of the bacterial community structure in monkeys with ALD. Differences of the relative abundances of gut microbiota at phylum, order, family, genus and species levels were observed between control monkeys and monkeys with ALD, and different pathways enriched in the monkeys with ALD were identified by metagenomic function analysis. Firmicutes, Proteobacteria, Verrucomicrobia tended to increase whereas Bacteroidetes and Actinobacteria decreased in the fecal microbiota of ALD group compared to the control group. Lactobacillales and Lactobacillus significantly decreased in ALD monkeys compared with normal monkeys, Streptococcus is lower in the ALD group compared with the control group. The nonhuman primate model of ALD will be useful for exploration of the microbiome markers as diagnosis and potentially prognosis for ALD. The ALD model will benefit the development of new therapeutic procedures for treating ALD and provide safety and efficacy evaluation for clinical application.